“What Was the First Book Printed in the Philippines?” - Totanes, Vernon R. (Journal of Philippine Librarianship; Vol 28 No 1 (2008), 2009)
Provides a brief overview of book history and determines the first book published in the Philippines. Briefly illustrates the stages of book life cycle: publication, manufacture, distribution, reception and survival. It analyzes the research made by Pardo de Tavera and Retana regarding the printing and existence of the Tagalog Doctrina and Shih-lu. Totanes concludes that "the Tagalog Doctrina and the Shih-lu were written by non-Filipinos, printed by non-Filipinos and were meant to be read by non-Filipinos."
Keywords: Shih-lu; Doctrina Christiana